Oral Feedback for Learner’s Language Development - Yusofi, Vindy Nita; Asmiyah, Siti; Muhtarom, Muhtarom (ICONELT, 2022)
In ELT there are many types of oral feedback that can be used by teachers to respond and correct the mistakes of language learners. However, there are still many teachers who have difficulty or less reflection in choosing the appropriate feedback for students. Therefore, this study aimed to identify the important role of the types and ways in giving oral feedback by an English teacher in language learner development. This study uses a content analysis method using secondary data taken from the previous study in the form of journal articles and thesis published in Indonesian and International journal sites in the past two decades. The result of this study revealed that from 2009 to 2021 there were many changes regarding the application of oral feedback. However, it was found that corrective feedback always be used continuously from year to year, while one of the most dominant types of oral feedback used was explicit feedback.